EFEKTIVITAS TOKEN ECONOMY DALAM MENINGKATKAN KEDISIPLINAN SANTRI MENJAGA KEBERSIHAN - Didi Riyadi; Yohandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2023)
The token economy or valuable card technique is one of the many techniques in the behavioral approach. The token economy method is very similar to what is encountered in real life, for example, workers are paid for their work. The purpose of this research is to describe the effectiveness of the token economy in increasing the discipline of students in maintaining cleanliness. The type of research used is (action research). Based on the results of research regarding the lack of discipline in maintaining cleanliness and assistance as well as special handling using token economy techniques, it can be concluded that; In cycle I, special assistance and handling by using the token economy, there were a few changes that were still far from perfect. In cycle II, special assistance and handling carried out by researchers using token economy techniques can increase the discipline of students in maintaining cleanliness. Thus special assistance and handling using the token economy technique is effective in increasing the discipline of students in maintaining cleanliness